Effects of Changing the Reporting System from Decentralized/Modality-Based to Centralized/Subspecialized Radiology on Radiologists, Radiologic Technicians and Referring Physicians of a Multi-Center Radiology Network. Issue 1 (16th September 2021) - Zabel, Andreas; Leschka, Sebastian; Fischer, Tim; Wildermuth, Simon; Dietrich, Tobias
Objectives: To determine the effects of reorganizing a radiology institute from decentralized/modality-based to centralized/subspecialized radiology on radiologists, radiologic technicians, and referring physicians at a multi-center radiology network. Material and Methods: In 2017/2018 our multi-center radiology network was changed from decentralized/modality-based to centralized/subspecialized reporting. A survey was conducted among radiologists, technicians and two groups of referring physicians (main hospital and non-main hospitals). The following items were tested: Overall satisfaction, perceived quality of radiological reports, subjective productivity/efficiency, confidence of radiologists in their subspecialty, availability of radiologists and turnaround time. Two of five answering options on a 5-point Likert scale were considered to represent agreement. The Mann-Whitney-U-test served for statistical analyses in agreement before and after reorganization in each group. Results: For radiologists, a significant difference was observed in perceived quality of radiological reports 42/46 (91.3%) compared to 51/52 (98.1%; p = 0.013). For technicians, no significant differences were observed. In the group of main hospital referring physicians, significant differences were observed in overall satisfaction 129/152 (84.9%) compared to 164/174 (94.3%; p < 0.001) and in perceived quality of radiological reports 125/148 (72.8%) compared to 157/170 (92.4%; p = 0.001). In the group of non-main hospital referring physicians no significant differences were observed. Conclusion: The reorganization resulted in a significantly higher perceived quality of radiological reports for the groups of radiologists and main hospital referring physicians besides overall satisfaction for main hospital referring physicians. Specialized main hospital referring physicians value reports of specialized radiology, whereas less specialized, non-main hospital referring physicians did not experience any significant effect.